The territorial aspect of the development of the logistics supply chain (Journal of Economic Research & Business Administration, 2024)
This article explores the role of territorial logistics in the integration of Kazakhstan's regions into the global economy. The main purpose of the article is to consider the territorial aspect of the development of the logistics supply chain in Kazakhstan and its impact on ensuring sustainable and balanced economic growth. The analysis of the key problems and challenges facing the country is carried out, as well as recommendations for improving territorial logistics to support the development process are proposed.The study includes an analysis of the concept and strategy for the development of the transport logistics industry in Kazakhstan until 2030. The authors consider government programs such as «Nurly Zhol» and the National Development Plan until 2025 to identify key challenges and opportunities related to the country's territorial logistics and transport system. To achieve this goal, various analysis methods are used, including document analysis, bibliometric analysis and structural synthesis of transport systems.That article emphasizes the importance of territorial logistics to ensure sustainable development and increase the efficiency of the use of territorial resources. Territorial logistics is considered as an integrated approach to the management of spatial aspects of economic activity, including the organization and optimization of transport flows at the regional and urban levels. In conclusion, the article highlights new ways for the research and development of this field in Kazakhstan. A review of current research in the field of territorial logistics shows the versatility of research interest and the importance of further research for the development of effective strategies for managing logistics processes at the territorial level.Key words: Territorial logistics, territorial transport systems, regional transport systems.